How to prioritize patients and redesign care to safely resume planned surgery during the COVID-19 pandemic: A clinical validation study. (24th February 2021) - Logishetty, Kartik; Edwards, Thomas C.; Subbiah Ponniah, Hariharan; Ahmed, Marriam; Liddle, Alexander D.; Cobb, Justin; Clark, Callum
Abstract : Aims: Restarting planned surgery during the COVID-19 pandemic is a clinical and societal priority, but it is unknown whether it can be done safely and include high-risk or complex cases. We developed a Surgical Prioritization and Allocation Guide (SPAG). Here, we validate its effectiveness and safety in COVID-free sites. Methods: A multidisciplinary surgical prioritization committee developed the SPAG, incorporating procedural urgency, shared decision-making, patient safety, and biopsychosocial factors; and applied it to 1, 142 adult patients awaiting orthopaedic surgery. Patients were stratified into four priority groups and underwent surgery at three COVID-free sites, including one with access to a high dependency unit (HDU) or intensive care unit (ICU) and specialist resources. Safety was assessed by the number of patients requiring inpatient postoperative HDU/ICU admission, contracting COVID-19 within 14 days postoperatively, and mortality within 30 days postoperatively. Results: A total of 1, 142 patients were included, 47 declined surgery, and 110 were deemed high-risk or requiring specialist resources. In the ten-week study period, 28 high-risk patients underwent surgery, during which 68% (13/19) of Priority 2 (P2, surgery within one month) patients underwent surgery, and 15% (3/20) of P3 (< three months) and 16% (11/71) of P4 (> three months) groups. Of the 1, 032 low-risk patients, 322 patients underwent surgery. Overall, 21 P3 and P4 patients were expedited to 'Urgent' based on biopsychosocial factors identified by the SPAG. During the study period, 91% (19/21) of the Urgent group, 52% (49/95) of P2, 36% (70/196) of P3, and 26% (184/720) of P4 underwent surgery. No patients died or were admitted to HDU/ICU, or contracted COVID-19. Conclusion: Our widely generalizable model enabled the restart of planned surgery during the COVID-19 pandemic, without compromising patient safety or excluding high-risk or complex cases. Patients classified as Urgent or P2 were most likely to undergo surgery, including those deemed high-risk. This model, which includes assessment of biopsychosocial factors alongside disease severity, can assist in equitably prioritizing the substantial list of patients now awaiting planned orthopaedic surgery worldwide. Cite this article: Bone Jt Open  2021;2(2):134–140.